Success factors of under-prepared students: a phenomenological study - Felix, Oscar, author; Banning, James H., advisor; Miser, Keith M., advisor; Ahuna, Linda, committee member; Shang, Paul, committee member; Sherwood, Grant, committee member; Hughes, Blanche M., committee member (Colorado State University. Libraries, 2002)
This study examined success factors of eight under-prepared students at Colorado State University. The goal of the research was to understand the factors that allow students with low levels of academic preparation to succeed at a selective institution. Under-preparedness results from weak academic experiences in high school, often as a result of the student's low-income and first generation college family background. The research approach for this study utilized a phenomenological form of qualitative inquiry. This approach seeks to understand the essence or the "central underlying meaning" of an individual's experience. The factors which led to academic success for the eight students emerged from interview data. Four major themes emerged from the data: Pre-College Experiences; Struggles; Positive Campus Experiences and Support; and Student Growth. The Pre-College Experiences theme explored the events and experiences of the students prior to college enrollment. Their high school experiences reveal an expected pattern of poor academic preparation that low-income students tend to receive. The Struggles theme documented the challenges of being the first in the family to go to college, the academic struggles the students faced on campus- particularly during their first year and their social challenges. The theme on Positive Campus Experiences and Support documented the many services and people who made a positive impact on the students' social and academic life. The students received assistance from committed and caring professors and staff who provided encouragement, guidance, and constructive feedback. The advice created meaningful relationships and brought a sense of connectedness for the students. The students also developed successful academic strategies through observation, association, or imitation of other students. The Student Growth theme covered the transformation of the neophyte students into sophisticated scholars. Through their accumulation of successes, the students began to develop pride, confidence and independence. The students experienced tough times and endured the pain of low academic preparation. Despite of these struggles, the students revealed a strong sense of adaptation and perseverance. The sense of adaptation was exemplified by their ability to turn challenges into motivators, particularly the first generation college status. A potential source of shame was turned into a reason to excel. The students became accountable for their own academic responsibilities and internalized their motivation to graduate. In the end, the students took control not only of their academic life, but of their entire life. The findings were conceptualized within a student resiliency framework to explain the inordinate amount of perseverance of the eight students. According to Henderson and Milstein, resiliency can be taught through a six step curriculum. Understanding the factors which lead to academic success, and implementing a resiliency skills curriculum, can help under-prepared students enjoy a higher level of success.
Keywords: higher education; educational sociology